2009
DOI: 10.1074/jbc.m109.016337
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Direct Cyclic Nucleotide Modulation of mEAG1 and hERG1 Channels Revealed with Fluorescence and Electrophysiological Methods

Abstract: Similar to CNG and HCN channels, EAG and ERG channels contain a cyclic nucleotide binding domain (CNBD) in their C terminus. While cyclic nucleotides have been shown to facilitate opening of CNG and HCN channels, their effect on EAG and ERG channels is less clear. Here we explored cyclic nucleotide binding and modulation of mEAG1 and hERG1 channels with fluorescence and electrophysiology. Binding of cyclic nucleotides to the isolated CNBD of mEAG1 and hERG1 channels was examined with two independent fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 70 publications
7
122
1
Order By: Relevance
“…Moreover, the mEAG1 structure supports the idea that the bound intrinsicligand conformation seems to be a conserved feature of all CNBHDs. Such an observation explains the absence of cyclic nucleotide binding to the mEAG1 CNBHD, as previously shown (Brelidze et al, 2009). Further biochemical characterization suggests that the mEAG1 CNBHD may exists in the unliganded conformation.…”
Section: Structure Of the Mouse Eag1 Channel Cnbhdmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, the mEAG1 structure supports the idea that the bound intrinsicligand conformation seems to be a conserved feature of all CNBHDs. Such an observation explains the absence of cyclic nucleotide binding to the mEAG1 CNBHD, as previously shown (Brelidze et al, 2009). Further biochemical characterization suggests that the mEAG1 CNBHD may exists in the unliganded conformation.…”
Section: Structure Of the Mouse Eag1 Channel Cnbhdmentioning
confidence: 51%
“…Not surprisingly, the overall structure of the CNBHD shows the characteristic features of previously determined CNBHDs from mEAG and zELK channels (Figure 2), including the self-liganded conformation. The C-terminal residues Y727 to M729 of β9 are bound in similar positions when compared with cyclic nucleotides in HCN CNBDs, explaining the lack of direct modulation of agERG channels by cyclic nucleotides (Brelidze et al, 2009(Brelidze et al, , 2012(Brelidze et al, , 2013.…”
Section: Structure Of the Mosquito Erg Channel Cnbhdmentioning
confidence: 98%
“…All KCNH channels, including EAG1, contain a cyclic nucleotide-binding homology domain (CNBHD) in their carboxyl-terminal region that shares sequence and structural similarity with the CNBD of HCN channels (18 -20). The CNBHD in KCNH family channels does not bind cyclic nucleotides, and these channels are not directly regulated by cAMP or cGMP (18,21). However, we found that flavonoids such as fisetin bind to the CNBHD of EAG1 to stabilize the channel's open state (16,22).…”
mentioning
confidence: 66%
“…A longer protein composed of the entire C-linker and CNBD was used for fluorescence resonance energy transfer (FRET) experiments. This protein (HCN2 C-linker/CNBD -L586W) included residues 443-645 and a tryptophan substituted for a leucine at position 586 (21). For protein expression, the DNA encoding HCN2 C-linker/CNBD -L586W was subcloned into the pETGQ vector (27).…”
Section: Methodsmentioning
confidence: 99%
“…In cyclic nucleotide-regulated channels there are extra helices that connect the channel pore to the CNB domain and are responsible for transmitting the cAMP-induced conformational change to the pore; this region is known as the C-linker (Craven & Zagotta, 2006). Importantly, it has been well demonstrated that KCNH channel function is not affected by cyclic nucleotides and that the CNB-homology domain from KCNH channels does not bind nucleotides (Brelidze et al, 2009). Here, we describe the protocols for purification and crystallization of the CNB-homology domain from one of the members of the KCNH family, the mouse EAG channel.…”
Section: Introductionmentioning
confidence: 99%